Stereoselective Total Synthesis of Rhoiptelol B via Prins Cyclization - Yadav, Jhillu S.; Rahman, Md. Ataur; Reddy, N. Mallikarjuna; Prasad, Attaluri R.; Al Khazim Al Ghamdi, Ahmad (Synlett, 2014)
The stereoselective total synthesis of rhoiptelol B, a diarylheptanoid isolated from Rhoiptelea chiliantha is described. The tetrahydropyran ring was constructed by using Prins cyclization. The key steps involved in this synthesis are Prins cyclization, Mistunobu inversion, cross metathesis, Sharpless asymmetric dihydroxylation, and hydrogenolysis.
Keywords: rhoiptelol B; natural products; diarylheptanoid; Prins cyclization; Mitsunobu inversion